(untitled) (Gilgameš, 2019)
Many scholars have written about Amm. XXXI, 16, 9, paragraph in which Ammianus qualifies himself as miles quondam et Graecus. Generally, it is possible to distinguish two interpretations: it could be a biographic reference or an apology due to his presumed incompetence as latin writer. Starting from the comparison between the whole passage, the two prefaces (XV, 1, 1 and XXVI, 1, 1-2) and other chapters, this paper wants to stress the complexity of Ammianus work and his awareness as a literary man, giving particular importance to the adverb quondam.